Amphibious hearing in spotted seals (Phoca largha): underwater audiograms, aerial audiograms and critical ratio measurements - Sills, Jillian M.; Southall, Brandon L.; Reichmuth, Colleen (Journal of Experimental Biology, 2014)
Spotted seals ( Phoca largha ) inhabit Arctic regions that are facing both rapid climate change and increasing industrialization. While little is known about their sensory capabilities, available knowledge suggests that spotted seals and other ice seals use sound to obtain information from the surrounding environment. To quantitatively assess their auditory capabilities, the hearing of two young spotted seals was tested using a psychophysical paradigm. Absolute detection thresholds for tonal sounds were measured in air and under water over the frequency range of hearing, and critical ratios were determined using octave-band masking noise in both media. The behavioral audiograms show a range of best sensitivity spanning four octaves in air, from approximately 0.6 to 11 kHz. The range of sensitive hearing extends across seven octaves in water, with lowest thresholds between 0.3 and 56 kHz. Critical ratio measurements were similar in air and water and increased monotonically from 12 dB at 0.1 kHz to 30 dB at 25.6 kHz, indicating that the auditory systems of these seals are quite efficient at extracting signals from background noise. This study demonstrates that spotted seals possess sound reception capabilities different from those previously described for ice seals, and more similar to those reported for harbor seals ( Phoca vitulina ). The results are consistent with the amphibious lifestyle of these seals and their apparent reliance on sound. The hearing data reported herein are the first available for spotted seals and can inform best management practices for this vulnerable species in a changing Arctic.